Home or hospital: Where to deliver a child?-realities, uncertainties, and challenges of safe childbirth in Nepal. - Wagle, Rajendra R. (2005)
SUMMARY: 1. Background :The debate on the safety and women's right of choice to a home delivery vs. hospital delivery has settled for the development countries, but the relevance and importance of this debate to a developing country like Nepal is not fully appreciated. Childbirth is a risk-producing event and timely and adequate medical care for women who experience obstetric complications is an option for mitigating the risk. The unanswered question is not whether we need skilled attendance at labour but how skilled attendance for labour should be organized specially in a developing country with high maternal mortality and morbidity. The overall objective of this thesis is to identify factors which make women more likely to deliver either at home or in hospital. It is also aimed to provide a critique of the role of this home hospital divide as a process indicator for maternal mortality for the overall purpose of organizing maternity care in Nepal. 2. Methods :This study was done in an administratively and geographically well-defined territory of central Nepal with a population of 88, 547. Two study populations were identified. One comprised of women who recently delivered and another pregnant women with 26-34 weeks of gestation. The second study population was interviewed twice; during pregnancy and postpartum. Two questionnaires were developed. The first questionnaire contained questions on socio-economic variables, reproductive history, antenatal care and place of delivery in current pregnancy from the first study population, and baseline information from the second study population. Multiparous women who delivered last time in hospital, among the second study population, were also asked about their perception of risk, distance, cost and quality of care received in the hospital last time. The second questionnaire was for the interview after delivery and contained questions about time of onset of labour, time taken to decide to seek medical help and to reach the hospital after the decision was made, if hospital was attended, and complications of childbirth. For the stud of shifting of place of birth from the previous one, multiparous women from both study population were studied. 3. Results:There were 308 women in socio-economic distance and place of delivery study. There were 312 women in the second population group. The lower the socio-economic status and the more distant a pregnant woman lives from a maternity hospital, the more likely she is to delilver at home. Living farther than one hour away is 8 times and low amenity score status is 4 times more likely to lead to home delivery. The mother's education lower than primary, not having antenatal care and multiparity are associated with a higher chance of home delivery. perception of higher risk during pregnancy, has a high risk for hospital delivery. Perception of distance, cost and quality of maternity care were not associated with place of delivery. Almost 15% of the women do not go the same place to deliver as at the previous delivery. The multivariate analysis showed that living more than half an hour away from the maternity hospital was 2.7(CI 1.1-6.2) times higher risk of shifting their birthplace from hospital to home. Three and more parous women had a 4.2 (CI 1.8-9.6) times higher risk of shifting their birthplace from hospital to home. Living within one hour of reach to the maternity hospital was 3.1 (CI1.1-8.7) times higher and women with 2 parity compared with 3 or more had 4.7 (CI 1.5-15.1) times higher risk of shifting their birthplace from home to hospital. When women go to hospital for the delivery they are required to present to hospital at a prestipulated stage of labour. If she presents earlier than the exact 4 cm of cervical dilatation she will be refused admission. This is detrimental to her health. Eleven women were refused admission and had five times higher risk of complications. Thus not only place but temporal dimension is also very important for management of labour and as a whole maternity care organization. The medium duration of normal labour (first and second stages) was 10.7hrs, 13.8 hrs. in primiparous and 8.8 hrs. in multiparous. 44% of the whole population decided to seek medical help and the median duration of time taken for taking the decision to seek medical help was 7 hrs, 4 hrs less than the median duration of normal labour found in the study. Women who had an agricultural occupation had a higher median duration of decision-making than with other occupations. 35% of the whole population reached the hospital and the median duration of time needed to reach the maternity hospital from the time the decision was made was 1.25 hrs. Distance was the sole predictor of higher duration of median duration to reach hospital after decision was made to seek medical help. 4. Conclusion:The lower the socio-economic status and the more distant a pregnant woman lives from the maternity hospital, the more likely the risk of delivering at home. Place of birth is not static for all pregnancies as 15% of multiparous women have this phenomenon of 'shifting of birthplace ' . Shifting of birthplace can be linked with Nepalese women's attempt to influence the modern maternity care system to achieve safe delivery within the boundaries and geography of her conflinement. The perception of high risk influences women to deliver at hospital. At the same time, perception of distance, cost or quality of maternity care which the women received in last delivery are not associated with place of delivery. A professional definition of risk status may not be sufficient to advice women on the utilization of maternal health services in meaningful way, and women's perception of risk may be the right candidate to incorporate women's perspective to the factors that predict where she will delilvee her child. When women go to hospital for delivery they are required to present at the hospital at a prestipulated stage of labour. She will be refused admission, if she presents earlier than the exact 4 cm of cervical dilatation. This is detrimental to her health as it was found that she had five times higher risk of complications than those who were not refused admission. Beside place of delivery, temporal dimension was also studied. The median duration of normal delivery was 10.7 hrs, 13.8 hrs. in primiparous and 8.8 hrs in multiparous. 44% of the whole population decided to seek medical help was 7 hrs , in 4 hrs less than the median duration of normal labour found in the study. 35% of he whole population reached the hospital and the median duration of time needed to reach the maternity hospital from the time the decision was made was 1.25 hrs. These findings are not equivalent to delay. With continuing high proportion of home deliveries in developing countries, we may have to question the concept of delay in maternity care and its usefulness in its organization. A needed for a policy regarding place of delivery, specifically home delivery is overdue. Home deliveries should have a legitimate place in the scheme of organization of maternity care in Nepal. Although at first glance, the finding that 50% of women delivering in hospital and 11% of women having caesarean section seems an ideal description of a population who has received adequate Emergency Obstetric Care (EmOC), the findings suffer from ecological fallacy. Both home and hospital deliveries should be included and define whether all had EmOC so as to develop a meaningful process indicator of quality maternity care. Delivery starts at home and for many it ends at home. A process indicator which ignores this important stage of the process of maternity care, suffers inadequacies. Hospital delivery for some at present is a substitute for not comprehensively planning to meet intranatal care needs of all mothers to be.